Evaluating Photomath as a Classroom Formative Assessment Intervention: Effects on Grade 9 Learners’ Achievement in Radicals - Roziel Anne Basa; Douglas A Salazar (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: This study aims to evaluate Photomath application as a formative assessment intervention integrated into the classroom cycle to determine if it can improve Grade 9 learners’ achievement levels in solving radicals and to explore learners’ perceptions of the application as a formative assessment intervention. Methodology: The study used a one-group pretest–posttest design with qualitative support. Tools included a researcher-made 30-item achievement test, Photomath mobile application, and open-ended perception survey. The Wilcoxon Signed Ranks Test was applied for statistical analysis. Qualitative responses were examined through thematic analysis. Main Findings: Learners’ mean scores increased from 9.8 to 23.5, with all participants improving in the posttest. Most reached proficient or advanced levels. The Wilcoxon Signed Ranks Test showed a significant difference (p < 0.0001). Learners reported that the intervention helped in correcting errors and misconceptions, step-by-step understanding, and confidence in solving radicals. Novelty/Originality of this study: This study contributed to the classroom assessment policy by using Photomath specifically as a formative assessment mechanism, requiring learners to attempt solutions independently before checking the steps through the application. Findings imply that such use of Photomath helps improve learners’ achievement in radicals and enhances their understanding and confidence in solving mathematical problems.